Hindu gods in West Africa : Ghanaian devotees of Shiva and Krishna. - Wuaku, Albert. (Studies of Religion in Africa, 2013)
In Hindu Gods in West Africa , Wuaku offers an account of the histories, beliefs and practices of the Hindu Monastery of Africa and the Radha Govinda Temple, two Hindu Temples in Ghana. Using historical material and data from his field work in southern Ghana, Wuaku shows how these two Hindu Temples build their traditions on popular Ghanaian religious notions about the powerful magicality of India's Hindu gods. He explores how Ghanaian soldiers who served in the colonial armies in India, Sri Lanka, and Burma during World War II, Bollywood films, and local magicians, have contributed to the production and the spreading of these cultural ideas. He argues that while Ghanaian worshippers appropriated and deployed the alien Hindu religious world through their own cultural ideas,as they engage Hindu beliefs and rituals in negotiating challenges their own worldviews would change considerably.